A gas-slug model for basaltic Vulcanian eruptions at open-conduit volcanoes, constrained by textural characteristics and dynamics of the July 3rd, 2019, Stromboli eruption (Italy) - Giordano, Guido; Vona, Alessandro; Grillo, Teresa Oreade; Frontoni, Alessandro; Calabrò, Laura; Carrasco-Núñez, Gerardo; Aiuppa, Alessandro; Caricchi, Luca; De Astis, Gianfilippo; Di Genova, Danilo; La Spina, Giuseppe; Piochi, Monica; et al. (Volcanica, 2026)
Stromboli is a unique open-conduit mafic volcano known for persistent Strombolian eruptions of highly porphyritic (HP) basalticshoshonite scoria. Stronger paroxysmal explosions occur once or twice per decade, ejecting low porphyritic (LP) golden pumice from deeper volatile-rich magma. The July 3rd, 2019, paroxysm showed features of a Vulcanian eruption—supersonic blast, ballistic ejection, and pyroclastic flows—despite Stromboli’s open-conduit basaltic nature. Textural analysis suggests that LP pyroclasts formed via rapid decompression, fragmentation, and quenching. This event likely resulted from shallow HP-filled conduit pressurization and failure triggered by a rising large gas slug. This caused top-down decompression, evacuating both HP and deeper LP magma. The proposed “basaltic Vulcanian” model better fits geophysical data than the traditional deep LP magma ascent model.